Pengembangan SDM dan Pelatihan Kewirausahan Berbasis Potensi Lokal di Desa Tumpakoyot Bakung Blitar - Siti Kalimah; Achmad Asfi Burhanuddin; Moch. Azis Qoharuddin (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
This entrepreneurial training activity was held on August 15, 2018. Training materials are chosen according to the needs of the people in Tumpakoyot Village who have a lot of abundant potentials, namely Ketela, bananas and other potential but interest from small communities due to lack of skills and knowledge and lack of communication facilities in terms of marketing the product. Therefore, in Tumpakoyot Village, Bakung District, Blitar Regency held entrepreneurship training to improve the economic level of the community. Devotional activities that have been carried out in the form of human resources development and local potential-based entrepreneurial management training which include providing materials and training to make products by utilizing the products of the community, and after the finished product promotion and marketing as well as the importance of packaging and labelling on the resulting products. Where in this service we help the community to how to promote products by utilizing media, as well as making interesting new labels to put on the packaging that will be on the market as well as installing small banners in as a means of promotion. It is hoped that with this devotional activity, this can increase the number of customers/consumers because of the original domestic products.